Innovative Strategies in Educational Administration Management at MTs An-Nashir - Salma Gania; Astuti Darmiyanti (al-Afkar, Journal For Islamic Studies, 2024)
The educational administration management strategy at MTs An-Nashir involves the integration of financial applications, student data collection, and teacher administration. The use of applications such as "MTs An-Nashir Financial Cash Application," "Emis," and "Simpatika" shows efforts to increase efficiency and integration in the administrative process. Focusing on the security and sustainability of student data is also a priority. In addition, innovation with the educational setting and the enthusiastic involvement of stakeholders, including parents, also support the development of schools as dynamic learning centers. This research aims to explain innovative educational administration strategies in school institutions. This research was conducted with teachers and principals at MTs An-Nashir as research subjects. The methodology employed in the research uses qualitative methods. The study's findings demonstrate that the administrative management strategies carried out by teachers and principals have improved the youngsters' lives of MTs An-Nashir.